Public first aid education model design study based on user experience - Luo, Jing; Zheng, Kaiqiao; Hong, Wudi (Frontiers in Public Health, 2023)
Background Presently, China’s first aid penetration rate remains relatively low, leaving ample room for improvement in the existing first aid education model. Given its role as a service for the general public, public first aid education must thoroughly consider the learning needs and experiences of the public when designing the teaching mode. Methods Semi-structured interviews were employed to gather detailed insights into participants’ experiences in the first aid learning process. Subsequently, NVivo was utilized to analyze the interviews and identify specific design strategies. Additionally, a 7-point scale questionnaire was employed to assess the intervention effects of music familiarity and the simulation of teaching aids on users’ willingness and confidence in learning. Building upon the design strategy, a “feedback device + app” approach was proposed. Finally, user satisfaction was evaluated through a scale questionnaire. Results The use of familiar music had a significant positive effect on participants’ willingness and confidence to learn, while users’ fear of teaching aids had no effect on willingness and confidence. The user experience-based first aid education model can better meet the public’s learning needs for first aid knowledge and skills. Conclusion This study proposes a first aid education model based on user experience design methodology, which optimizes the public’s self-learning experience by evoking positive emotions while circumventing negative emotions. The educational model was recognized by users in terms of design concepts and is expected to help increase first aid prevalence in the future.